Omvänt eller bakvänt? - Per Ole Träskman (Nordisk Tidsskrift for Kriminalvidenskab)
The International human rights demand that the prosecutor has the burden of proof. During the last years, new provisions concerning confiscation, especially in narcotic offence cases, have been introduced in some countries, e.g., England, The Netherlands and Germany. These provisions make it possible to confiscate possessions held by a suspected person, without really proving that the property originates from crime. The prosecuted person can avoid confiscation by proving that he has obtained the property in a legal way. Such a confiscation provision was introduced also in Danish law in 1997.